2024
DOI: 10.1039/d3na00748k
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale investigations of femtosecond laser induced nanogratings in optical glasses

Qiong Xie,
Nadezhda Shchedrina,
Maxime Cavillon
et al.

Abstract: The intrinsic structure of nanogratings imprinted in silica by femtosecond laser direct writing is composed of light-aligned oblate nanopores. These nanogratings are at the origin of the strong form birefringence exploitable to write various optical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Modeling studies of bulk nanogratings are usually based on a low dielectric constant seed as an initial "nanovoid" [15,20]. Some studies have suggested point defects like E'; ODC; and, generally, color centers [21], as well as transient defects like self-trapped electrons (STEs) [18,45] and self-trapped holes (STHs) [22] as seeds. In discussing potential precursors, we must consider the necessity of a lower change in the refractive index to facilitate the plasma field enhancement perpendicularly to light polarization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling studies of bulk nanogratings are usually based on a low dielectric constant seed as an initial "nanovoid" [15,20]. Some studies have suggested point defects like E'; ODC; and, generally, color centers [21], as well as transient defects like self-trapped electrons (STEs) [18,45] and self-trapped holes (STHs) [22] as seeds. In discussing potential precursors, we must consider the necessity of a lower change in the refractive index to facilitate the plasma field enhancement perpendicularly to light polarization.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested above, glass free volume could serve as a primary seed for the nanocavitation process. The rapid transition from nanoplasma hotspots into nanopores is driven by swift temperature transfer to phonons and local thermal expansion, which effectively imprints oblate nanopores [18]. These nanopores' shapes and orientations are largely influenced by the incident light's polarization, supporting a plasma-mediated over a thermo-mediated nanocavitation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation